Responsabilidade socioambiental e empresas: uma análise no setor privado da região metropolitana de João Pessoa-PB - Silva, Danielly Ferreira da (2012)
Constant political, social and economic pressures have been driven enterprises to assume a more committed social and environmental posture. The social responsibility has acquired major importance for the society and the business sector. This latter, it has performed a key role in the enhancement of the socio-environmental behavior and survival in the competitive market. Thus, companies have adopted strategies to interact with environmental responsibility, such as environmental management and education, green economy and marketing; and expand its field of operation. In the metropolitan area of João Pessoa, Paraíba, environmental responsibility became part of the society and business environments. In this study, we analyze how environmental responsibility has been applied in private companies from the metropolitan area of João Pessoa by applying qualitative approach and some quantitative procedures. Analysis comprises literature review, document analysis, telematic research and systematic observation in the companies, questionnaires and interviews with environmental managers and/or companies CEO, including managers of 5 companies that belong to the construction, cement, plastic, graphic and accommodations sectors. The perception of stakeholders covered the internal public and customers/consumers of the Hotel. With these results it was possible identify environmental conducts, noting that the majority of companies have a reasonable level of the socio-environmental context understanding where they recognize their responsibility and the importance of socio-environmental programs as well as advantages for the company. Socio-environmental practices are aimed at controlling and preventing impacts being focused on employees.